2021
DOI: 10.3390/ijms22042039
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Hypertrophy and Compensatory Increase in Systolic Function in a Mouse Model of Oxidative Stress

Abstract: Free radicals, or reactive oxygen species, have been implicated as one of the primary causes of myocardial pathologies elicited by chronic diseases and age. The imbalance between pro-oxidants and antioxidants, termed “oxidative stress”, involves several pathological changes in mouse hearts, including hypertrophy and cardiac dysfunction. However, the molecular mechanisms and adaptations of the hearts in mice lacking cytoplasmic superoxide dismutase (Sod1KO) have not been investigated. We used echocardiography t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The Adenine group had a significantly higher stroke volume index, LV ejection fraction, and LV mass when compared to the Control group. An increased or preserved ejection fraction has been associated with both systolic ( 34 ) and diastolic ( 35 ) dysfunction in non-CKD mouse models. An increase in stroke volume index and ejection fraction usually occurs due to volume overload, which commonly presents in dialysis patients and is an important prognostic factor in determining interventional outcome ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Adenine group had a significantly higher stroke volume index, LV ejection fraction, and LV mass when compared to the Control group. An increased or preserved ejection fraction has been associated with both systolic ( 34 ) and diastolic ( 35 ) dysfunction in non-CKD mouse models. An increase in stroke volume index and ejection fraction usually occurs due to volume overload, which commonly presents in dialysis patients and is an important prognostic factor in determining interventional outcome ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the HAO1 have reported its highest expression value in G2 by 2.89-fold compared to the control group (p≥0.05, Figure2). The oxidative stress is known as the the changes between antioxident level and prooxidant [48]. The gradual significant increase of HAO1 resulted in the increasing of oxidative stress.…”
Section: Relative Gene Expression Rspo2 Hao1 and Runx Genesmentioning
confidence: 99%